Penerapan Manajemen Risiko menggunakan Metode FMEA pada Proyek Penggalian Sumur Bor oleh CV. Tirto Kencana - Ignatius Jevon; Jani Rahardjo (Jurnal Titra, 2021)
This research was conducted to analyze the causes of potential risks during construction projects at CV. Tirto Kencana. The study was conducted using the Failure Mode Effect and Analysis (FMEA) method. FMEA method is a commonly used method in identifying and analyzing potential risk factors in order to solve problems. After conducting the analysis, it was found that the potential risks that occurred were caused by negligence in making the agreement document during the procurement or tender stage process and negligence at the work implementation stage. The root of the problem is the problem when making the work agreement document and the problem of natural factors that occur when the technical work takes place.